Biotemplated facile synthesis of three‐dimensional micro/nanoporous tin oxide: improving the flammable and mechanical properties of flexible PVC. (24th July 2019) - Meng, Weihua; Wu, Weihong; Zhang, Weiwei; Cheng, Luyao; Jiao, Yunhong; Qu, Hongqiang; Xu, Jianzhong
Abstract : In this study, a flame retardant [Pollen‐type SnO2 (P‐SnO2 )] with a micro/nanoporous structure was synthesised by the simple immersion–calcination method using pollen as a biological template. When applied into flexible polyvinyl chloride (PVC), PVC composite adding P‐SnO2 (PVC/P‐SnO2 ) exhibited much better mechanical property than that adding commercial SnO2 (PVC/[C‐type SnO2 (C‐SnO2 )] for the results that the tensile strength and impact toughness are increased by 11.3 and 37.9%, respectively. Moreover, PVC/P‐SnO2 has always the same flame retardancy and smoke suppression abilities compared with PVC/C‐SnO2 . It provides a method using biotemplate for preparing metal oxide flame retardants with both great flame retardant and toughening properties.